#### Answer

A

#### Work Step by Step

The equation $x^{2}-4x-12=0$ can easily be solved by factoring as shown below:
$x^{2}-4x-12=0$
$x^{2}+2x-6x-12=0$
$x(x+2)-6(x+2)=0$
$(x+2)(x-6)=0$
$x+2=0$ and $x-6=0$
$x=-2$ and $x=6$

Published by
Cengage Learning

ISBN 10:
1285194055

ISBN 13:
978-1-28519-405-9

A

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.